2021
DOI: 10.7150/ijms.54508
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma fatty acid-binding protein 3 is related to prolonged corrected QT interval and reduced ejection fraction in patients with stable angina

Abstract: Background: Higher concentrations of plasma fatty acid-binding protein 3 (FABP3) play a role in the development of cardiovascular events, cerebrovascular deaths, and acute heart failure. However, little is known about the relationship between plasma FABP3 level and prolonged QT interval and reduced ejection fraction (EF). This study aimed to investigate the relationship between plasma FABP3 level and prolonged corrected QT (QTc) interval and reduced EF in patients with stable angina. Inflammatory cytokine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…More specifically, the pericardial fat secretome has been associated with reduced I Kr and increased I CaL currents in metabolic syndrome, resulting in APD prolongation ( 18 ). Serum levels of the adipokine fatty-acid binding protein has also been suggested as a biochemical proxy for prolonged QTc interval and reduced ejection fraction in patients with stable angina ( 19 ). Similarly, plasma adiponectin may modulate ventricular repolarisation and thereby QTc interval ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the pericardial fat secretome has been associated with reduced I Kr and increased I CaL currents in metabolic syndrome, resulting in APD prolongation ( 18 ). Serum levels of the adipokine fatty-acid binding protein has also been suggested as a biochemical proxy for prolonged QTc interval and reduced ejection fraction in patients with stable angina ( 19 ). Similarly, plasma adiponectin may modulate ventricular repolarisation and thereby QTc interval ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most (but not all) studies investigating the relationship between FABP3 and atrial remodeling have shown evidence for a contribution of FABP3 to the atrial remodeling and AF based on FABP3 plasma levels or tissue messenger RNA (mRNA) (14)(15)(16)(17). From a mechanistic perspective, the protein concentration of FABP3 in the RA may be better suited to reflect the correlation between FABP3 regulation and RA function.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid-binding protein 3 (FABP3) is an intracellular FA carrier, which has been evaluated as a biomarker of atrial maladaptive remodeling in patients with metabolic disease (12,13). Correlation of the plasma levels and genetic expression of FABP3 with atriomyopathy suggest a relation between FABP3 expression in the atrial tissue and atrial function; however, this has not yet been explored (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of evidence supports the notion that both FABP3 and FABP4 serum concentrations can predict both all-cause [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ] and CV mortality [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]; however, the potential role of these FABPs as predictive biomarkers for the mortality risk among subjects with T2D and chronic HF (CHF) has not been explored yet. Thus, the aim of this study was to assess the prognostic value of these two FABPs (i.e., FABP3 and FABP4) for both all-cause and CV mortality in outpatient CHF subjects with T2D.…”
Section: Introductionmentioning
confidence: 93%